The distance learning course on computer networks at the university of Coimbra - Silva, João Costa e (2014)
João Costa e Silva, Sandra Pedrosa, Maria José Marcelino, António Mendes, Fernando Boavida, Mário Bernardes, "The Distance Learning course on Computer Networks at the University of Coimbra”, proceedings of CompSysTech 2014 - 15th International Conference on Computer Systems and Technologies, pp. 386-392, Ruse, Bulgaria, 27 June 2014. DOI: 10.1145/2659532.2659640